Marine Resource Inventory and Mapping Strategy Based on Correlation Analysis to Support Sustainable Development Policies - Ali, Moh. Mudassir; Darise, Ramla Ilham (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2025)
This study integrated marine resource inventory and mapping in 119 villages across 10 sub-districts in Tolitoli Regency. The objective was to identify marine potential spatially and evaluate its suitability with regional development policies. A mixed method approach was employed, employing field surveys, interviews, questionnaires, and Geographic Information System (GIS)-based geospatial mapping. A total of 120 respondents were selected through purposive sampling, and the data were analyzed descriptively, using correlational analysis, and using factor analysis using SPSS. The results indicate that imbalanced resource allocation is a major obstacle in the marine sector. Marine energy potential has not been optimally utilized, while Tolitoli's strategic location opens up untapped opportunities for international cooperation. These findings underscore the importance of implementing the Blue Economy concept and integrating  SDG14 into regional planning. This research contributes to data-driven, adaptive, and collaborative coastal development policies.